Late mucosal ulcers in dose-escalated adaptive dose-painting treatments for head-and-neck cancer. (1st February 2018) - Olteanu, Luiza Ana Maria; Duprez, Fréderic; De Neve, Wilfried; Berwouts, Dieter; Vercauteren, Tom; Bauters, Wouter; Deron, Philippe; Huvenne, Wouter; Bonte, Katrien; Goethals, Ingeborg; Schatteman, Julie; De Gersem, Werner
Abstract: Background: To identify predictive factors for the development of late grade 4 mucosal ulcers in adaptive dose-escalated treatments for head-and-neck cancer. Material and methods: Patient data of four dose-escalated three-phase adaptive dose-painting by numbers (DPBN) clinical trials were analyzed in this study. Correlations between the development of late grade 4 ulcers and factors related with the treatment, disease characteristics and the patient were investigated. Dosimetrical thresholds were searched among the highest doses received by 1.75 cm 3 (D1.75cc ) of the primary gross tumor volume (GTVT ) and the corresponding normalized isoeffective dose (NID21.75cc, with a reference dose of 2Gy/fraction and α/β of 3 Gy). Results: From 39 studied patients, nine developed late grade 4 mucosal ulcers. The continuation to either smoke or drink alcohol after therapy was the factor that showed a strong (eight out of nine patients) association with the occurrence of grade 4 ulcers. Six of the patients who continued to smoke or/and drink had D1.75cc and NID21.75cc above 84 Gy and 95.5 Gy, respectively. Seven of the patients with grade 4 had the dose levels above these thresholds, but even if the D1.75cc threshold was significant in the prediction of late grade 4 ulcers, it could not be considered as the only contributing factor. Conclusions: The search for patterns provided strong reasons to apply a dosimetrical threshold for the peak-dose volume of 1.75 cm 3 as a preventive measure for late grade 4 mucosal ulcers. Also, patients that continue to smoke or drink alcohol after therapy have increased risk to develop late mucosal ulcers.